Our relationships, our values, our culture - Aboriginal young men's perspectives about sex, relationships and gender stereotypes in Australia. Issue 3 (1st March 2023) - Graham, Simon; Martin, Kacey; Beadman, Mitchell; Doyle, Michael; Bolt, Reuben
Abstract: Studies of Aboriginal young people have often followed a deficit approach depicting them as 'risky' and in need of help. In contrast, this study took a strengths-based approach and focussed on what Aboriginal young people value, how they stay safe and how their culture impacts their lives. 16 Aboriginal men aged 16 to 24 years were interviewed in Sydney, Australia. We examined Aboriginal young men's perspectives about relationships, sex and gender. Interviews were conducted by young Aboriginal men in 2019 and 2020. Overall, four features of positive sexual and romantic relationships were discussed: (1) love, connection and support; (2) enjoyment and fun; (3) responsibility, safety and consent; and 4) honesty, respect and trust. Additionally, three topics related to gender roles: (1) becoming a man; (2) sex as a masculine achievement; and (3) inequality and gender stereotypes. Our study suggests that Aboriginal young men are exploring sexual and romantic relationships, and although they value enjoyment and fun, they are aware of broader issues such as consent and respect. The young men acknowledged gender stereotypes faced by young women. Our results could be used by future school safe sex education programmes to better meet the needs of Aboriginal young men.